Prospect of Wave Energy in Malaysia - Zahari, Taha; Nahidul Hoque , Samrat; Norhafizan, Ahmad; Choudhury, I.A. (2014)
In developing country like Malaysia, the demand for electricity is expected to rise with increasing urbanization and rapid industrialization. Currently energy production is mainly dependent on fossil fuel but in the near future fossil fuels will not be sustainable because of the depletion of existing reserves and their impact on the environment. Wave energy is an environmentally friendly and fastest growing renewable energy source for a sustainable electrical power generation of the future. Unlike others renewable energy resources, wave energy can produce electric power all over the year. As Malaysia has a total coastline of 4,675 kilometers so there is a great potential for utilization of wave energy in Malaysia especially along the coast and the islands. This paper presents a feasibility study of wave energy at different locations in Malaysia including the estimation of the total power available from the seas surroundings Malaysia. Furthermore, the analysis of investment, operation and maintenance cost for a wave farm is also presented.